Liberalism, Liberalization and Their Impacts of Muslim Education (Special Case of Indonesian Intellectuals) - Hamid Fahmy Zarkasyi (TSAQAFAH, 2012)
This paper is aimed at elucidating the liberalization of Muslim world and its impact on education. For  that  purpose  the  author  traces  at  the  outset  the  origin  and  the  basic  concept  of liberalism, which  is of  postmodern Western worldview, including  the concept of  religious liberalism. The impact of  liberalism in general is as wider as the meaning of  liberalism in Western sense of the words. However,  this paper  confines only on  the study of  their  impact  on Muslim education with special emphasis on national education policy and on religious thought which in turn would affect curriculum development. Liberalization of religious thought appears, inter alia, through the introduction  of  the  doctrine  of  relativity  of  truth,  religious  pluralism,  gender  equality  and deconstruction  of  shari’ah  and  the  likes. All  those  religious  discourse  conceptually  hinder  the development of  curriculum and  the teaching strategy of  moral  inculcation  to the students.